Metabolomics‐based pathway changes in testis fragments treated with ethinylestradiol in vitro. Issue 20 (26th July 2019) - Sun, Jinchun; Beger, Richard D.; Sloper, Daniel T.; Nakamura, Noriko
Abstract: Background: There is a need to develop in vitro models to test drugs and chemicals that induce toxicity in the male reproductive system. We have evaluated an in vitro mouse testis organ culture model capable of producing viable, fertilization‐proven sperm as a possible toxicity test model. Although this in vitro model was limited to round spermatid differentiation, histopathology observations could still be performed. Liquid chromatography/mass spectrometry analysis (LC/MS)‐based metabolomics was used to measure metabolome changes of chemically treated in vitro testis fragments. Methods: On Postnatal Day 5, C57BL/6J mouse testes were divided into four fragments, which were placed onto a 1.5% agarose gel cube and cultured in α‐MEM including 0.4% AlbuMAX I (Day 0). On Day 1 of culture, testis fragments were treated with 0 (control), 0.01, or 1 nM ethinylestradiol (EE). On Day 20 of culture, the testis fragments were collected for LC/MS and histology analysis. Results: Several metabolites involved in glycogen metabolism and glycolysis pathways (uridine diphosphate‐glucose, glucose phosphate, and pyruvate), in the tricarboxylic acid cycle pathway (oxaloacetate and aspartate), and in the arginine and proline metabolism (arginine and spermine) were significantly altered in the 1 nM EE treated group compared to the control group. The metabolite changes were associated with an increase in percentage of seminiferous tubules with round spermatids as well as dose‐dependent dead cells. Conclusion: These findings suggest that EE treatment may cause testicular toxicity by affecting glycogen metabolism and energy pathways. To confirm these findings, further experiments will be necessary using other testicular toxicants.